2022
DOI: 10.1093/chromsci/bmac027
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Venetoclax Concentration in Plasma Using High-Performance Liquid Chromatography

Abstract: Venetoclax is an oral B-cell lymphoma-2 protein inhibitor. It is a key drug for the treatment of chronic lymphocytic leukemia and acute myeloid leukemia. However, venetoclax is administered at a fixed dose, irrespective of body surface area or weight. Furthermore, the plasma concentration of venetoclax varies widely between individuals and is influenced by diet. Therefore, individualized dosing using therapeutic drug monitoring (TDM) may help to optimize treatment in clinical practice. In this study, we aimed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Presently, research on monitoring serum Venetoclax concentration during treatment is still less. To our knowledge, there are only two methodological studies published [ 29 , 30 ], and no clinical intervention study is performed to prove the effect of serum drug concentration on treatment safety. Both the two existing studies reported that the steady-state trough concentration of Venetoclax during treatment in AML patients fluctuated in a range of 250–8000 ng/ml.…”
Section: Discussionmentioning
confidence: 99%
“…Presently, research on monitoring serum Venetoclax concentration during treatment is still less. To our knowledge, there are only two methodological studies published [ 29 , 30 ], and no clinical intervention study is performed to prove the effect of serum drug concentration on treatment safety. Both the two existing studies reported that the steady-state trough concentration of Venetoclax during treatment in AML patients fluctuated in a range of 250–8000 ng/ml.…”
Section: Discussionmentioning
confidence: 99%
“…Blood samples were collected before and six hours after VEN administration, and the minimum (C min ) and maximum plasma concentrations (C max ) were measured. The VEN concentration in the patients' plasma was measured using highperformance liquid chromatography-ultraviolet 4 .…”
Section: Pharmacokinetic Analysismentioning
confidence: 99%
“…Although these methods had a relatively low quantitative lower limit, analytical run-time was longer and larger plasma sample sizes are not suitable for paediatric samples. In the published literature, either the lower limit of quantification was high or the analysis time was too long [11,12]. Compared with these methods, our method only needed 50 μL plasma samples, the analysis time was 5 min, and the lower limit of quantification was 10 μL mL À1 .…”
Section: Acta Chromatographicamentioning
confidence: 99%